2014
DOI: 10.1039/c3lc51421h
|View full text |Cite
|
Sign up to set email alerts
|

Geometric effect of the hydrogel grid structure on in vitro formation of homogeneous MIN6 cell clusters

Abstract: A microstructure-based hydrogel was employed to study the relationship between spatial specificity and cellular behavior, including cell fate, proliferation, morphology, and insulin secretion in pancreatic β-cells. To effectively form homogeneous cell clusters in vitro, we made cell-containing hydrogel membrane constructs with an adapted grid structure based on a hexagonal micropattern. Homogeneous cell clusters (average diameter: 83.6 ± 14.2 μm) of pancreatic insulinoma (MIN6) cells were spontaneously generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Recently, a new method, based on geometric effects of the hydrogel grid structure, presents a different view on the formation of b cell spheroids (Bae et al, 2014). In this method, b cells were encapsulated in hydrogels, which are crosslinked to a hexagonal grid structure.…”
Section: Other Methodsmentioning
confidence: 99%
“…Recently, a new method, based on geometric effects of the hydrogel grid structure, presents a different view on the formation of b cell spheroids (Bae et al, 2014). In this method, b cells were encapsulated in hydrogels, which are crosslinked to a hexagonal grid structure.…”
Section: Other Methodsmentioning
confidence: 99%
“…For the in vitro assay, MIN6 cells can be an adequate cell type replacing pancreatic beta cells that are limited to isolate from animal sources and no longer remain in their primary state of viability and function 26, 27 . In our previous work 23 , it was reported that MIN6 cells were clumped together as a multicellular cluster in a micropatterned free-standing hydrogel sheet; moreover, there was a functional improvement with inclusion of mesh micropatterns in the hydrogel sheet. On the basis of the advantages of hydrogel sheets as a cell-carrier module, here we reversibly integrated a layer of hydrogel sheet as an insertional module into a microfluidic device, with the aim to demonstrate the potential application of the hydrogel module-based multicellular analysis using MIN6 cell clusters.…”
Section: Introductionmentioning
confidence: 93%
“…These macro-scale sheet-like multicellular structures can provide (1) a simple and effective tool for the reorganization of cells due to micropatterned substrates 20, 21, 23 , (2) a large contact surface for simultaneous screening based on multiple arrayed cells, (3) an advanced artificial tissue layer by utilizing various cell types 20 , and (4) a novel application for large tissue-like multi-layered sheets 22, 24, 25 . Thus, hydrogel sheets can be applied as a tool to analyze multicellular structures integrated with microfluidic devices that require additional processes for individual rearrangement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Recently, the form of "freestanding biopaper" was expanded towards various 3D cell culture applications through layer-by-layer assembly and was demonstrated as a toolkit for biofunctional assays and cell proliferation assays. 23,24 An artificial 3D hepatic tissue reconstruction was demonstrated by assembling cellular hydrogel biopaper modules. Meanwhile, PDMS, a most commonly used polymer for simple manufacture of microfluidic devices, is unfamiliar to biologists and clinicians, and somewhat inflexible for long-term cell maintenance due to the medium evaporation and metabolite adsorption.…”
Section: Cell-containing Hydrogel Modules For 3d Cell Culturementioning
confidence: 99%